Getting started in health research - Bowers, David, 1938-; House, Allan; Owens, David, 1954- (Hoboken, NJ : John Wiley & Sons, 2011)
By the time you've read this book, you'll be ready to design your own research projectNot everyone in clinical research is a scientific investigator. In fact, a large proportion of health professionals undertaking a research project are working in clinical care, as junior doctors, nurses or allied health professionals. For them a book that begins with the basics of study design and takes them through all the stages to data collection, analysis, and submission for publication is vital. Getting Started in Health Research is the answer. It provides fundamental information on:Framing the research.
Front Matter -- Limbering up. Turning your General Aim into a Specific Question -- Taking a Preliminary Look at What has Already been done -- On your Marks. Coming up with an Initial Plan of Action -- Carrying out a Systematic Search -- Building a Team -- Get Set. Choosing the Best Study Design -- Selecting Samples for Quantitative Research -- Selecting Samples for Qualitative Research -- Wait for it. Deciding what Information to Collect -- Tackling Confounders -- How Many People to Study? -- Getting Ready for a Qualitative Analysis -- Getting Ready for a Quantitative Analysis -- Writing your Final Protocol -- Arranging Funding -- Getting Permission to go Ahead -- Go!. Recruiting the Participants -- Collecting and Recording the Data -- Living with (and without) the Data -- Staying the Course. Taking Stock -- Making Sense of your Results b6 (BThe Quantitative Case -- Making Sense of your Results b6 (BThe Qualitative Case -- The Finishing Line. Writing a Research Paper -- Setting Out your Findings -- Writing your Discussion -- Writing a Thesis or other Report -- Dealing with Journals -- Further Reading -- Index.s
Includes bibliographical references and index.
Keywords: Medicine -- Research; Biology -- Research; Biomedical Research -- methods; Science; Medicine; MEDICAL -- Research; Biology -- Research; Medicine -- Research; Electronic books